2018
DOI: 10.1148/radiol.2018170577
|View full text |Cite
|
Sign up to set email alerts
|

Renal Allograft Dysfunction: Evaluation with Shear-wave Sonoelastography

Abstract: Purpose To evaluate whether shear-wave sonoelastography can help differentiate stable renal allograft from acute allograft dysfunction and chronic allograft dysfunction and to correlate shear-wave sonoelastography measurements with resistive index (RI), serum creatinine level, estimated glomerular filtration rate (eGFR) obtained with the Nankivell equation, and biopsy findings. Materials and Methods A prospective study of 60 patients who had undergone renal transplantation was conducted between October 2014 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
4
20
1
Order By: Relevance
“…Furthermore, the patients with allograft dysfunction had a significantly higher stiffness at the cortex as compared to those with stable allograft function (p-value < 0.02). The values of the tissue stiffness at cortex in our study are similar to those reported by Ma et al [23], but the medians are slightly higher as compared to the values reported by Ghonge et al for chronic allograft dysfunction (24.50 kPa ± 4.49 (range, 17.07-32.98 kPa)) [22]. Grenier et al [48] performed a pilot study and quantified the kidney allograft stiffness using supersonic shear imaging (SSI) [49] that use two spatially extended plane shear waves and consequently enlarge the area of available information.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the patients with allograft dysfunction had a significantly higher stiffness at the cortex as compared to those with stable allograft function (p-value < 0.02). The values of the tissue stiffness at cortex in our study are similar to those reported by Ma et al [23], but the medians are slightly higher as compared to the values reported by Ghonge et al for chronic allograft dysfunction (24.50 kPa ± 4.49 (range, 17.07-32.98 kPa)) [22]. Grenier et al [48] performed a pilot study and quantified the kidney allograft stiffness using supersonic shear imaging (SSI) [49] that use two spatially extended plane shear waves and consequently enlarge the area of available information.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the small number of patients with kidney allograft dysfunction, these results need to be validated on larger cohort. Previous studies have reported significant correlation of kidney allograft stiffness with eGRF (negative), RI (positive) and serum creatinine level (positive) (p-values < 0.05) [22,50,51]. The positive correlation of parenchymal stiffness with serum creatinine level could reflect the link between allograft function and stiffness, but this relation was not proven in our study, nor in the study conducted by Brocchi et al [52].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…A more recent prospective study to evaluate the value of SWS for the differentiation of stable allograft function from acute and chronic allograft dysfunction was performed by Ghonge et al The study revealed that SWS can help to differentiate stable allograft function from acute and chronic dysfunction in addition to laboratory and Doppler-based parameters [37].…”
Section: Ultrasoundmentioning
confidence: 99%